ANALISIS PEMIKIRAN MUHAMMAD SYAHRUR TENTANG PEMBAGIAN WARISAN 2:1 PERSPEKTIF HUKUM ISLAM - EkaPratama, Ibnu (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2025)
This article explores Muhammad Shahrur’s perspective on the distribution of inheritance in Islam, particularly concerning the principle that allocates a male heir twice the share of a female heir (2:1). Historically, this provision has been an integral component of the Islamic inheritance system (mawarith), grounded in Qur’anic verse An-Nisā’ (4:11). However, within the framework of contemporary social realities—especially where women also serve as primary breadwinners—this rule invites renewed questions regarding its relevance and equity. Shahrur introduces an alternative hermeneutical approach through his theory of hudud (maximum and minimum limits), arguing that the 2:1 ratio represents an upper boundary rather than an immutable rule. This article employs a library research method with a focus on content analysis. The findings indicate that while Shahrur's thought opens up possibilities for a more contextual reinterpretation of Islamic inheritance law, it also provokes significant controversy due to its departure from the classical scholarly consensus, which tends to apply inheritance verses in a literal and fixed manner.